1996
DOI: 10.1161/01.cir.94.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Vitamin C Improves Endothelial Dysfunction in Chronic Smokers

Abstract: The present studies demonstrate that the antioxidant vitamin C markedly improves endothelium-dependent responses in chronic smokers. This observation supports the concept that endothelial dysfunction in chronic smokers is at least in part mediated by enhanced formation of oxygen-derived free radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
260
4
20

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 520 publications
(301 citation statements)
references
References 21 publications
17
260
4
20
Order By: Relevance
“…Supplementation of smokers with 2000 mg vitamin C per day for 10 days significantly reduced monocyte adhesion to cultured endothelial cells (Weber et al, 1996). Heitzer et al (1996) and Motoyama et al (1997) observed increased vasodilation in smokers given an infusion of 10-18 mg vitamin C/min (or a total dose of about 1000 mg). The longer-term effects of vitamin C on endothelial function have been studied in patients with coronary artery disease (Gocke et al, 1999).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Supplementation of smokers with 2000 mg vitamin C per day for 10 days significantly reduced monocyte adhesion to cultured endothelial cells (Weber et al, 1996). Heitzer et al (1996) and Motoyama et al (1997) observed increased vasodilation in smokers given an infusion of 10-18 mg vitamin C/min (or a total dose of about 1000 mg). The longer-term effects of vitamin C on endothelial function have been studied in patients with coronary artery disease (Gocke et al, 1999).…”
Section: Discussionmentioning
confidence: 94%
“…Oxidized LDL (OxLDL) in turn may induce endothelial expression of adhesion molecules, like intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) (Penn & Chisolm, 1994;Holvoet, 1999). Previous reports (Celermajer et al, 1993;Zeiher et al, 1995;Heitzer et al, 1996) have suggested that smoking induces endothelial dysfunction, which is regarded as an early event in atherogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That ascorbate is beneficial to the endothelium in vivo is also supported by clinical studies of endothelium-dependent vasodilatation in patients with endothelial dysfunction due to atherosclerosis Heitzer et al, 2001;Tousoulis et al, 2005) and related conditions, including hypertension (Duffy et al, 1999;Duffy et al, 2001;Taddei et al, 1998), smoking (Heitzer et al, 1996;Kaufmann et al, 2000;Solzbach et al, 1997), and diabetes (Tousoulis et al, 2007). Many of the studies in atherosclerosis used high doses of intravenous ascorbate to acutely demonstrate this improvement in endothelial function in humans.…”
Section: Endothelial Cellsmentioning
confidence: 90%
“…The adverse effects of smoking on vascular function have been examined in human subjects. These studies have shown that acute and chronic cigarette smoking impairs nitric oxide synthase (Zeiher et al, 1995;Silvestrini et al, 1996;Heitzer et al, 1996). However, a consensus of the causal relationship between electro physical disorders of the heart and consumption of smoking and smokeless tobacco has not yet been reached.…”
Section: Discussionmentioning
confidence: 99%